Pooled prevalence and associated factors of overweight/obesity among under-five children in 46 low- and middle-income countries: A cross-sectional analysis of Demographic and Health Surveys data (2015–2024) - Dejen Kahsay Asgedom; Fentahun Bikale Kebede; Simachew Getaneh Endalamew; Bewuketu Terefe; Solomon Keflie Assefa; Etsay Woldu Anbesu (PLOS Global Public Health, 2026)
Overweight and obesity remain major global public health challenges, particularly among children under five years of age in low- and middle-income countries (LMICs). This study aimed to assess the pooled prevalence of overweight/obesity and its associated factors among children aged 6–59 months in 46 LMICs. We used the most recent nationally representative demographic and health surveys (2015–2024) from forty-six LMICs. A total of 393,638 weighted samples of children aged 6–59 months were included. Childhood overweight and obesity were defined as weight-for-height greater than two and three standard deviations above the WHO reference population median, respectively. Multilevel log-binomial regression models were employed. An adjusted risk ratio ( R R ) with a 95% confidence interval (CI) was used to select variables that had a significant association with childhood overweight/obesity. A p value < 0.05 was used to declare statistical significance. The data were analyzed with R software (version 4.5.1). The pooled prevalence of overweight/obesity was 3% (95% CI: 2.44, 3.58), with significant regional variation ranging from 1.62% in West Africa to 10% in the Europe and Central Asia (95% CI: 5.26, 17.84). Male sex (RR = 1.07, 95% CI: 1.03, 1.11), larger-than-average birth size (RR = 1.66, 95% CI: 1.54, 1.78), facility delivery (RR = 1.20, 95% CI: 1.13, 1.27), maternal smoking (RR = 1.61, 95% CI: 1.38, 1.87), maternal overweighed/obesity (RR = 2.37, 95% CI: 2.19-2.56), media exposure (RR = 1.05, 95% CI: 1.01, 1.10), and rich (RR = 1.10, 95% CI: 1.04, 1.16) household wealth were factors associated with increased risk. Children aged 24–59 months had lower risk compared to those aged 6–23 months. Protective factors included current breastfeeding (RR = 0.91, 95% CI: 0.87, 0.95), interpregnancy intervals 18–23 months (RR = 0.77, 95% CI: 0.71, 0.83), and ≥ 24 months (RR = 0.87 95% CI: 0.83, 0.91), and multiple births (RR = 0.67, 95% CI: 0.57, 0.79). Contextually, children in medium–human development index (HDI) (RR = 1.80, 95% CI: 1.62, 2.00) and higher–HDI countries (RR = 3.57, 95% CI: 3.00, 4.24) had elevated risk. Compared to West Africa, all other regions showed significantly higher risk, with Europe & Central Asia demonstrated the strongest association (RR = 3.37, 95% CI: 2.90, 3.91). The pooled prevalence of overweight/obesity among under-five children in LMICs is relatively low compared to high-income nations, yet substantial regional variation exists. Male sex, larger size at birth, maternal smoking, maternal overweight/obesity, higher household wealth quantiles and higher-HDI were associated with increased risk of childhood overweight/obesity, whereas current breastfeeding and longer interpregnancy intervals were protective. These findings highlight the importance of close monitoring of the problem and region-specific interventions targeting modifiable risk factors.